Common law equity, and American public administration - Green, Richard T. (2002)
This article evaluates the claims of those who advocate the use of common law as a corrective to the statutory and rule-based excesses of the American administrative state. Their claims are assessed in light of common-law history and in terms of current administrative law. Although many claims are exaggerated or simply wrong, there are some aspects of common law that deserve attention in public administration. These are explained from the perspective of common-law evolution. Common law developed in a very pragmatic and experimental fashion and therefore displays some qualities public administrators will find useful, especially in the adjudicative realm of agency decisions, but more broadly as well. A model with five features of common-law practice is presented for public administrators to use in improving an agency's decision making under law. - Reproduced.
Keywords: Public administration